2019
DOI: 10.1002/jpln.201800472
|View full text |Cite|
|
Sign up to set email alerts
|

Under drought conditions NaCl improves the nutritional status of the xerophyte Zygophyllum xanthoxylum but not of the glycophyte Arabidopsis thaliana

Abstract: Zygophyllum xanthoxylum is a salt‐accumulating xerophytic species with excellent adaptability to adverse environments. Previous studies demonstrated that Z. xanthoxylum absorbs a great quantity of Na+ as an osmoregulatory substance under arid conditions. To investigate the nutritional status of Z. xanthoxylum in comparison with a typical glycophyte, Arabidopsis thaliana, seedlings were exposed to NaCl (50 mM for Z. xanthoxylum and 5 mM for A. thaliana), osmotic stress (–0.5 MPa), and osmotic stress combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…K + , Na + , Ca 2+ , and Mg 2+ were extracted from dried plant tissues in 100 mM acetic acid (Sangon, Shanghai, China) at 90°C for 2 h ( Wang et al, 2019), and then the K + , Na + and Ca 2+ concentrations were determined using a flame spectrophotometer (Model 410 Flame; Sherwood Scientific, Ltd., Cambridge, UK) ( Wang et al, 2004), and the Mg 2+ concentration was determined using an atomic absorption spectrophotometer (AAS, AA‐670, Shimadzu, Kyoto, Japan) ( Wang et al, 2019). The Cl − , H 2 PO4 - , SO4 2- , and NO3 - in the oven‐dried tissues were extracted with deionized water at 100°C for 2 h, and then Cl − , H 2 PO4 - , and SO4 2- were assessed by ion chromatography (ICS 2000, DIONEX, Sunnyvale, USA) ( Yang et al., 2008), and NO3 - was detected by a colorimetric method using a UV spectrophotometer as described by Drechsler et al.…”
Section: Methodsmentioning
confidence: 99%
“…K + , Na + , Ca 2+ , and Mg 2+ were extracted from dried plant tissues in 100 mM acetic acid (Sangon, Shanghai, China) at 90°C for 2 h ( Wang et al, 2019), and then the K + , Na + and Ca 2+ concentrations were determined using a flame spectrophotometer (Model 410 Flame; Sherwood Scientific, Ltd., Cambridge, UK) ( Wang et al, 2004), and the Mg 2+ concentration was determined using an atomic absorption spectrophotometer (AAS, AA‐670, Shimadzu, Kyoto, Japan) ( Wang et al, 2019). The Cl − , H 2 PO4 - , SO4 2- , and NO3 - in the oven‐dried tissues were extracted with deionized water at 100°C for 2 h, and then Cl − , H 2 PO4 - , and SO4 2- were assessed by ion chromatography (ICS 2000, DIONEX, Sunnyvale, USA) ( Yang et al., 2008), and NO3 - was detected by a colorimetric method using a UV spectrophotometer as described by Drechsler et al.…”
Section: Methodsmentioning
confidence: 99%
“…Majority of the cultivated plants consist of glycophyte species, which are comparatively sensitive to this particular parameter (Wang et al, 2019). Furthermore, such property is highly accurate for bell peppers or Capsicum annuum L., which is otherwise one of the primarily ingested fruits globally (Erel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our research further demonstrated that 50 mM NaCl could alleviate the deleterious impacts on the growth of SX Zygophyllum xanthoxylum under drought stress Ma et al 2012;Nan et al 2016). In addition, the addition of Na + could also promote the uptake of the important nutrients in Z. xanthoxylum, such as Ca 2+ , Mg 2+ , nitrate (N), and phosphate (P), which contributes to stimulating growth of Z. xanthoxylum and alleviating the deleterious effect of osmotic stresses (Ma et al 2016;Wang et al 2019). Soils in arid regions are deficient in mineral nutrients; however, the SX species can absorb and harness nutrients especially Na + to enhance drought resistance; therefore, adding appropriate Na + in the soil may contribute to enhancing drought tolerance and accelerate the development of desert SX species.…”
Section: Introductionmentioning
confidence: 99%